In vitro Synergistic Antibacterial Effect of Ozonized Antarctic Krill Oil in Combination with Antibiotics against Bacterial Skin Pathogens. Issue 1 (2nd January 2021) - Kim, Hong-Deok; Lee, Soo-Bin; Eom, Sung-Hwan; Yu, Daeung; Cho, Suengmok; Kim, Young-Mog; Kim, Seon-Bong
ABSTRACT: Ozonized Antarctic krill oil (OAKO) exhibited a significant antibacterial activity against bacterial skin pathogens that cause various skin infectious diseases such as Propionibacterium acnes, Staphylococcus epidermidis, Staphylococcus aureus, and Pseudomonas aeruginosa . Minimum inhibitory concentration (MIC) values of OAKO against these bacteria ranged from 128 to 256 μg/ml. Furthermore, MIC values of antibiotics such as erythromycin and lincomycin were dramatically reduced in combination with OAKO against antibiotic-resistant bacteria. The combination of OAKO with erythromycin exhibited significant synergistic effect with fractional inhibitory concentration (ΣFIC) 0.375 and 0.503 against erythromycin-resistant P. acnes and P. aeruginosa, respectively. Hence, these results indicate synergistic antibacterial effects of restoration traditional antibiotics with OAKO.